2022
DOI: 10.3389/fpubh.2022.749033
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions for Prevention of Common Infections Among Opioid Users: A Systematic Review of Systematic Reviews

Abstract: BackgroundThe North American opioid crisis is marked by high opioid-related mortality and morbidity, including opioid use-associated infections (OUAIs). Users of pharmaceutical and non-pharmaceutical opioids are at an increased risk of acquiring hepatitis C (HCV), human immunodeficiency virus (HIV), and other infections. No high-level evidence, however, has been synthesized regarding effectiveness of interventions to prevent OUAIs in legal, and illegal/mixed opioid users. The aim of the study is to synthesize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Implementation of needle-exchange programs (NEPs) is one intervention that has gained considerable support, with clear benefits in terms of preventing HIV transmission [41,42]. Studies on sole-NEP intervention to prevent HCV; however, have been inconclusive, with a meta-analysis showing mixed results [43][44][45]. Notably, a systematic review conducted by Platt et al (2018) found high NEP coverage in Europe to be associated with a reduction in HCV acquisition risk, but no effect was observed in North America [46].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of needle-exchange programs (NEPs) is one intervention that has gained considerable support, with clear benefits in terms of preventing HIV transmission [41,42]. Studies on sole-NEP intervention to prevent HCV; however, have been inconclusive, with a meta-analysis showing mixed results [43][44][45]. Notably, a systematic review conducted by Platt et al (2018) found high NEP coverage in Europe to be associated with a reduction in HCV acquisition risk, but no effect was observed in North America [46].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have only been observational studies in which each of these components, particularly their combination, has been associated with reductions in HIV and/or HCV infection risk [4][5][6]. The traditional criteria for grading quality of evidence in systematic reviews automatically assess evidence from observational studies as low, and therefore, evidence for the effect of comprehensive NSP and OAT participation has been deemed to be of low quality [4,7]. Despite this 'low quality' evidence, the World Health Organization (WHO) strongly recommends a comprehensive package of HRP to reduce transmission of HIV, HCV and hepatitis B virus (HBV) among PWID [8].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to HAV (hepatitis A virus) and HBV, there are currently no effective vaccines against HCV [19,20] and HIV [21]. However, harm reduction programmes including OAT and needle and syringe programmes, which have been established in Switzerland since the early 1990s [22,23], reduce the risk of HCV and HIV infection [24][25][26][27][28]. Besides, since 2012, guidelines recommend antiretroviral treatment (ART) irrespective of CD4 count [29], lowering the community viral load and contributing to reduced HIV transmission (treatment as prevention) [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%